Analysis of the Characteristics of Nitrogen and Phosphorus Emissions from Agricultural Non-Point Sources Pollution and Pollution Risk in Tianjin City, China. Issue 4 (February 2020) - Zhao, Jirui; Zhao, Wei; Zhan, Xianhui; Chen, Xiaoming; Wei, Daiyan; Ma, Nan; Sun, Meng; Liu, Jiahong; Xu, Yuan
Abstract: In order to understand the current status of agricultural non-point source pollution in Tianjin and figure out the main pollution source and areas, the evaluation and spatial distribution of agricultural non-point source pollution were analyzed. The pollution discharge coefficient method was used to estimate the agricultural non-point source pollution in Tianjin. The spatial distribution pattern of agricultural non-point source pollution load was analyzed by ArcGIS software, the pollution evaluation and sources analysis were carried out by equivalent pollution load method. The results show that the pollution load of TN and TP in Tianjin in 2017 was 11760.7 and 871.86 tonnes per year respectively, and the equivalent pollution loads were 11760.70 and 8718.68 m 3 separately. Among the districts, the Baodi District, Wuqing District and Jinghai District have higher pollution loads, which are the key control areas. The spatial analysis showed the similar distribution characteristics of pollution load and intensity, which was higher in the middle and lower in the north and south in Tianjin. It is necessary to separately develop targeted pollution prevention measures to strengthen management and control.